Military Chaplaincy, Moral Injury, Pastoral Narrative Disclosure, Bereavement and Spiritual Research Contamination - Carey, Lindsay B (Health and Social Care Chaplaincy, 2025)
This issue of Health and Social Care Chaplaincy presents research regarding the work of Ukrainian military chaplains at war. It also presents findings from the Australian Chaplaincy Moral Injury Skills Training (MIST) and Pastoral Narrative Disclosure (PND) programme for health and social care chaplains caring for veterans and/or first responder personnel on how to address issues relating to their occupational moral injury. In line with these topics, this issue also considers chaplaincy within the healthcare context providing support for families experiencing bereavement following a major trauma. Last, and by no means least, a warning is presented regarding the increasing use of contaminated scales in spirituality-related research.